440 Activity and safety of camrelizumab, an anti-PD-1 immune checkpoint inhibitor, for patients with advanced non-small-cell lung cancer. (10th December 2020) - Sun, Guo Gui; Jia, Jing Hao; Gao, Peng; Yao, Xue Min; Chen, Ming Da; Yao, Wei Nan; Sun, Lu; Wang, Wei
Abstract : Background: Effective options are limited for patients with non–small-cell lung cancer (NSCLC) whose disease progresses after first-line chemotherapy. Camrelizumab is a potent anti-PD-1 monoclonal antibody and has shown promising activity in NSCLC. We assessed the activity and safety of camrelizumab for patients with previously treated, advanced NSCLC patients with negative oncogenic drivers. Methods: Patients who progressed during or following platinum-based doublet chemotherapy were enrolled. All patients received camrelizumab(200 mg)every 3 weeks or in combination with chemotherapy until loss of clinical benefit. The primary endpoint was objective response rate (ORR), other endpoints included disease control rate (DCR), progression-free survival (PFS) and safety. Results: Between Aug 5, 2019, and Jun 19, 2020, we enrolled 29 patients, 25 patients were available evaluated, ORR and DCR was 36% (9/25) and 92% (23/25), respectively. 25 of 29 patients were still receiving the treatment, the median PFS was not yet achieved. Compared with those without reactive cutaneous capillary endothelial proliferation (RCCEP), patients with RCCEP had higher ORR (60% vs. 28.6%). Treatment-related adverse events (AEs) occurred in 69.0% of patients (all Grade), and the most common were RCCEP (37.9%), pneumonitis (6.9%), and chest congestion (6.9%). Treatment-related grade 3 to 4 adverse events occurred in 10.3% of patients. Conclusions: In patients with previously treated advanced NSCLC, camrelizumab demonstrated improved ORR and DCR, compared with historical data of the 2nd line chemotherapy, with a manageable safety profile. While patients with RCCEP derived greater benefit from camrelizumab. Further studies are needed in large sample size trials.